Impact of Eggshells on Growth and Production of Soybean (Glycine max(L) Merril) in Ultisol - Sari, Desi Pramida; Warnita, Warnita; Muhsanati, Muhsanati (International Journal of Environment, Agriculture and Biotechnology, 2023)
Soybean (Glycine max (L) Merril) is one of the agricultural commodities to help the food crop of the Indonesian people. Soybeans are one of the commodities that support the implementation of food crop diversification programs and support national food crop security. Increasing soybean productivity in ultisols can be done through liming using eggshell powder. This experiment has been implemented at Jalan Muhammad Hatta, RT 02, RW 08, Pauh, Padang, West Sumatera from October 2020 to March 2021. The purpose is to get the best eggshell powder dose to increase the growth and yield of the soybean on ultisol. The experiment method uses a complete random design (RAL) with 5 levels of eggshell powder treatment 0; 25; 50; 75; 100 g / plant. Data on the observation are analyzed statistically with the F test at a 5% level. If the F count of treatment is greater than the F table, proceed by the test DNMRT at α level of 5% level. The results showed the use of eggshell powder affected the growth and yield of soybean in ultisol to a dose is 25 g /plant.